2017
DOI: 10.4236/ojoph.2017.74033
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Retinal Detachment in Indonesia: Clinical Characteristics, Risk Factors, and Treatment Outcomes

Abstract: Purpose: To describe the clinical features and risk factors of pediatric retinal detachment among patients in Indonesia. Methods: This is a retrospective study involving 46 eyes of 34 children (younger than 18 years) diagnosed with pediatric retinal detachment. A detailed history was taken and a complete ophthalmic examination and a systemic examination were performed as required. Clinical characteristics, risk factors, and treatment choices were noted. Retinal detachment was categorized as tractional, exudati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…2 A study in Indonesia revealed that Coats disease is the most frequent cause of exudative retinal detachment in pediatric patients, accounting for 50% of the cases, despite the difficulty in screening. 3 The case was mostly found in the 11-15 year age group with a ratio of 3:1 of male and female new cases. 3,4 Most patients in Indonesia were treated with a combination of laser photocoagulation, cryotherapy, and vitreoretinal surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 A study in Indonesia revealed that Coats disease is the most frequent cause of exudative retinal detachment in pediatric patients, accounting for 50% of the cases, despite the difficulty in screening. 3 The case was mostly found in the 11-15 year age group with a ratio of 3:1 of male and female new cases. 3,4 Most patients in Indonesia were treated with a combination of laser photocoagulation, cryotherapy, and vitreoretinal surgery.…”
mentioning
confidence: 99%
“…3 The case was mostly found in the 11-15 year age group with a ratio of 3:1 of male and female new cases. 3,4 Most patients in Indonesia were treated with a combination of laser photocoagulation, cryotherapy, and vitreoretinal surgery. 3 The standard regiment of treatment mainly revolves around vascular ablation using laser photocoagulation or cryotherapy, or later on will be referred as standard focal therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation